A Cometary Fluorescence Model for the ν3 Vibrational Band of Cyanogen - P. Hardy; P. Rousselot; C. Richard; V. Boudon; X. Landsheere; A. Voute; L. Manceron; F. Kwabia Tchana (The Astrophysical Journal, 2025)
Cyanogen (C _2 N _2 ) has been suspected for a long time to be present in comets and to contribute to the creation of the CN radical. So far no observations with ground-based facilities have managed to detect this species, but the Rosetta mission, thanks to in situ observations with the ROSINA mass spectrometer, detected this species in the coma of 67P/Churyumov–Gerasimenko. To investigate its presence from infrared spectra in other comets, we developed a fluorescence model for the ν _3 fundamental band. From new laboratory high-resolution infrared spectra of cyanogen, we analyzed the region of the ν _3 band of C _2 N _2 , centered around 4.63 μ m (2158 cm ^−1 ). In addition to line positions and intensities, molecular parameters for the ground and excited vibrational state were obtained. These parameters allowed us to develop a fluorescence model for cyanogen. Line-by-line excitation rates of the ν _3 band of cyanogen in cometary comae are presented. An upper limit of the abundance of cyanogen in a spectrum of comet C/2022 E3 (ZTF) is discussed.